Medium and high voltage cable and method for manufacturing the same

CN122337769BActive Publication Date: 2026-10-30BEIJING TIANCHENG RUIYUAN CABLE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610774798.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-01
Publication Date
2026-10-30
Estimated Expiration
2046-06-01

AI Technical Summary

Technical Problem

[0004]第一,现有中高压电缆绝缘层与绝缘屏蔽层多采用三层共挤工艺直接结合,邻接界面处容易形成电阻率和热机械性能的阶跃突变,在负荷循环和机械应力作用下可能引发空间电荷积聚与界面应力集中;部分方案虽然尝试设置均质过渡层或多层配比递变层,但均质过渡层难以同时兼顾绝缘层侧的界面粘接需求和绝缘屏蔽层侧的导电功能衔接需求,多层配比递变层则仍可能在相邻层之间形成突变界面;

Benefits of technology

[0032]本发明有益效果为:本发明在绝缘层与绝缘屏蔽层之间设置连续梯度相容缓冲过渡层,使相容组分、导电填料含量及体积电阻率沿厚度方向连续变化,降低界面性能突变,减小空间电荷积聚和电场畸变,通过至少三股熔体分路共挤及分段冷却定型,提高过渡层与相邻层的熔融结合稳定性,减少界面扰动和热应力集中,从而提升中高压电缆的长期运行可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122337769B_ABST
    Figure CN122337769B_ABST
Patent Text Reader

Abstract

The application discloses a medium-high voltage cable and a preparation method thereof, and relates to the technical field of power cable materials and manufacturing, which comprises a conductor, a conductor shielding layer, an insulation layer, a gradient compatible buffer transition layer, an insulation shielding layer, a metal shielding layer, an inner lining layer, an armor layer and an outer sheath layer arranged in sequence from inside to outside; the gradient compatible buffer transition layer is arranged between the insulation layer and the insulation shielding layer, and the gradient compatible buffer transition layer is a continuous gradient layer formed by integrally co-extruding different semi-conductive polyolefin-based composite melts in radial order, cross-linking, and then retaining after segmented cooling. The application reduces space charge accumulation and electric field distortion, and improves the stability of the transition layer structure and the long-term operation reliability of the cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power cable materials and manufacturing technology, and in particular to a medium and high voltage cable and its preparation method. Background Technology

[0002] With the increasing demands for transmission and distribution capacity and operational reliability from urban power grids, rail transit, new energy grid connection, and industrial power supply and distribution systems, the application ratio of medium and high voltage cross-linked polyethylene insulated cables in power transmission and distribution networks is constantly increasing. Existing medium and high voltage cables typically include a multi-layer coaxial structure consisting of a conductor, conductor shielding layer, insulation layer, insulation shielding layer, metal shielding layer, and outer sheath. The insulation layer mainly serves the function of electrical insulation, while the insulation shielding layer is mainly used to homogenize the electric field on the outer surface of the insulation and cooperate with the metal shielding structure to form a stable electric field boundary. Since the insulation layer usually uses highly insulating cross-linked polyolefin materials, while the insulation shielding layer usually uses semi-conductive polyolefin composite materials containing conductive fillers, there are differences between the two in terms of volume resistivity, conductive filler content, polar components, melt rheological properties, and shrinkage behavior after cross-linking and cooling. This makes the interface region between the insulation layer and the insulation shielding layer an important part affecting the long-term stability of the cable insulation system.

[0003] There are still some technical shortcomings in the existing technology:

[0004] First, existing medium and high voltage cables often use a three-layer co-extrusion process to directly bond the insulation layer and the insulation shielding layer. This can easily lead to abrupt changes in resistivity and thermomechanical properties at the interface, which may cause space charge accumulation and interface stress concentration under load cycling and mechanical stress. Although some solutions attempt to set up a homogeneous transition layer or a multi-layer proportionally variable layer, the homogeneous transition layer cannot simultaneously meet the interface bonding requirements on the insulation layer side and the conductivity connection requirements on the insulation shielding layer side. The multi-layer proportionally variable layer may still form abrupt interfaces between adjacent layers.

[0005] Second, existing co-extrusion molding and cross-linking cooling processes are usually difficult to stably build and maintain a radially continuously changing composition and resistivity distribution in the thin-walled transition region. The transition region is easily affected by the melt composite state, cooling shrinkage differences and interfacial thermal stress, resulting in micro-region composition fluctuations, local discontinuities or decreased interfacial bonding strength, which affects the long-term operational reliability of the cable insulation system. Summary of the Invention

[0006] This invention provides a medium- and high-voltage cable, characterized in that it comprises, from the inside out, a conductor, a conductor shielding layer, an insulation layer, a gradient compatibility buffer transition layer, an insulation shielding layer, a metal shielding layer, an inner lining layer, an armor layer, and an outer sheath layer.

[0007] The gradient compatibility buffer transition layer is disposed between the insulating layer and the insulating shielding layer, and the gradient compatibility buffer transition layer is a continuous gradient layer formed by integral co-extrusion of multiple strands of semi-conductive polyolefin-based composite melts with different compositions in radial order and retained after cross-linking and segmented cooling.

[0008] The semi-conductive polyolefin-based composite material used in the gradient compatibility buffer transition layer includes a polyolefin matrix, conductive fillers, and compatibility components.

[0009] The gradient compatibility buffer transition layer, along its thickness direction from the side near the insulating layer to the side near the insulating shielding layer, exhibits a continuous monotonically decreasing content of compatibility components, a continuous monotonically increasing content of conductive fillers, and a continuous monotonically decreasing volume resistivity.

[0010] The gradient compatibility buffer transition layer does not have a layered interface, and the gradient compatibility buffer transition layer and the insulating layer, as well as the gradient compatibility buffer transition layer and the insulating shielding layer, are all directly fused interfaces.

[0011] In a preferred embodiment of the medium- and high-voltage cable described in this invention, the thickness of the gradient compatibility buffer transition layer is 0.05–0.12 mm.

[0012] By weight, the semi-conductive polyolefin-based composite material comprises 55-75 parts of polyolefin matrix, 20-30 parts of conductive filler and 6-12 parts of compatible component;

[0013] The compatible components include 5-10 parts grafted maleic anhydride polyethylene and 1-3 parts surface-modified nano silica.

[0014] In a preferred embodiment of the medium- and high-voltage cable of the present invention, the polyolefin matrix comprises low-density polyethylene and linear low-density polyethylene, and the mass ratio of the low-density polyethylene to the linear low-density polyethylene is 6:4 to 7:3; the conductive filler is acetylene black.

[0015] The surface-modified nano-silica has a particle size of 20–30 nm, and the modification method is plasma treatment or silane coupling agent modification.

[0016] As a preferred embodiment of the medium and high voltage cable of the present invention, the gradient compatibility buffer transition layer includes, along the thickness direction, a first gradient region, a second gradient region, and a third gradient region that are continuously transitioned together.

[0017] The content of compatible components in the first gradient region is higher than that in the second gradient region, and the content of compatible components in the second gradient region is higher than that in the third gradient region;

[0018] The conductive filler content in the first gradient region is lower than that in the second gradient region, and the conductive filler content in the second gradient region is lower than that in the third gradient region.

[0019] In a preferred embodiment of the medium- and high-voltage cable described in this invention, the volume resistivity of the gradient compatibility buffer transition layer near the insulation layer is 8.0 × 10⁻⁶. 4 ~1.3×10 5 The volume resistivity of the gradient compatibility buffer transition layer near the insulating shielding layer is 8.0 × 10 Ω·cm. 2 ~2.0×10 3 Ω·cm.

[0020] As a preferred embodiment of the medium- and high-voltage cable manufacturing method of the present invention, it includes the following steps:

[0021] S1. Provide a conductor and extrude a conductor shielding layer outside the conductor;

[0022] S2. Using a split-feed co-extrusion process, an insulating layer, a gradient compatibility buffer transition layer, and an insulating shield layer are integrally formed outside the conductor shield layer. Multiple strands of semi-conductive polyolefin-based composite melt forming the gradient compatibility buffer transition layer enter independent flow channels in the co-extrusion die head and undergo laminar flow composite in a radial order from the side closest to the insulating layer to the side closest to the insulating shield layer. The compositional differences between the individual melt strands and the coordinated control of temperature and melt flow state in each independent flow channel ensure that the gradient compatibility buffer transition layer exhibits a continuous gradient distribution during formation, with a continuously monotonically decreasing content of compatible components, a continuously monotonically increasing content of conductive fillers, and a continuously monotonically decreasing volume resistivity. Furthermore, the gradient compatibility buffer transition layer does not form a delamination interface and forms direct fusion bonding interfaces with the insulating layer and the insulating shield layer, respectively.

[0023] S3. Perform cross-linking treatment on the cable core obtained in step S2;

[0024] S4. Perform segmented cooling treatment on the cable core after cross-linking treatment in step S3. The segmented cooling treatment includes a first stage cooling and a second stage cooling, and the cooling rate of the first stage is lower than that of the second stage cooling, so as to retain the continuous gradient distribution and fusion bonding interface formed in step S2.

[0025] S5. The cable core after step S4 is degassed, and a metal shielding layer, an inner lining layer, an armor layer and an outer sheath layer are formed sequentially on the outside of the degassed cable core.

[0026] In a preferred embodiment of the medium- and high-voltage cable preparation method of the present invention, in step S2, the content of compatible components in each strand of semi-conductive polyolefin-based composite melt entering different independent flow channels decreases sequentially in the radial order, and the content of conductive filler increases sequentially in the radial order.

[0027] As a preferred embodiment of the medium and high voltage cable manufacturing method of the present invention, in step S2, the temperature in the independent flow channel is decreased sequentially in the radial order, and the melt flow state of each melt strand is differentially controlled in the radial order, so that each melt strand is laminarly compounded in the co-extrusion die head in the radial direction and forms a continuous transition connection between adjacent melt strands, thereby obtaining the gradient compatibility buffer transition layer without a layered interface inside.

[0028] As a preferred embodiment of the medium and high voltage cable manufacturing method of the present invention, in step S4, the first stage cooling is a slow cooling stage, and the second stage cooling is a shaping cooling stage;

[0029] During the segmented cooling process, a radial temperature gradient is maintained between the cable core and the cooling medium so that the gradient-compatible buffer transition layer maintains the continuous gradient distribution after crosslinking.

[0030] In a preferred embodiment of the medium- and high-voltage cable manufacturing method of the present invention, step S3 employs peroxide vapor crosslinking; step S5 employs vacuum degassing.

[0031] The metal shielding layer is a copper wire loosely wound metal shielding layer, the inner lining layer is a PVC inner lining layer, the armor layer is a galvanized steel strip armor layer, and the outer sheath layer is a high-density polyethylene outer sheath layer.

[0032] The beneficial effects of this invention are as follows: This invention sets a continuous gradient compatible buffer transition layer between the insulation layer and the insulation shielding layer, so that the compatible components, conductive filler content and volume resistivity change continuously along the thickness direction, reducing abrupt changes in interface performance, reducing space charge accumulation and electric field distortion. Through at least three melts co-extruded and segmented cooling and shaping, the stability of the fusion bonding between the transition layer and adjacent layers is improved, the interface disturbance and thermal stress concentration are reduced, thereby improving the long-term operational reliability of medium and high voltage cables. Attached Figure Description

[0033] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0034] Figure 1This is a diagram of the co-extrusion architecture of the gradient compatibility buffer transition layer in Example 1;

[0035] Figure 2 This is a flowchart of the medium and high voltage cable manufacturing process in Example 1. Detailed Implementation

[0036] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0037] Example 1

[0038] Reference Figure 1 and Figure 2 This is the first embodiment of the present invention. This embodiment provides a medium- and high-voltage cable and its manufacturing method. The medium- and high-voltage cable includes, from the inside out, a conductor, a conductor shielding layer, an insulation layer, a gradient compatibility buffer transition layer, an insulation shielding layer, a metal shielding layer, an inner lining layer, an armor layer, and an outer sheath layer.

[0039] A gradient compatibility buffer transition layer is disposed between the insulating layer and the insulating shielding layer. The gradient compatibility buffer transition layer is a continuous gradient layer formed by integral co-extrusion of at least three semi-conductive polyolefin-based composite melts with different compositions in a radial sequence, and is retained after cross-linking, segmented cooling and shaping. The at least three semi-conductive polyolefin-based composite melts adopt the same polyolefin matrix system, and the content of compatibility components and conductive fillers are set to vary in a radial direction.

[0040] The semi-conductive polyolefin-based composite material used in the gradient compatibility buffer transition layer includes a polyolefin matrix, a conductive filler, and a compatibility component. The compatibility component includes at least one of maleic anhydride-grafted polyolefin and surface-modified nano-silica.

[0041] Along its thickness direction, from the side closest to the insulating layer to the side closest to the insulating shielding layer, the content of the compatible component continuously and monotonically decreases, the content of the conductive filler continuously and monotonically increases, and the volume resistivity continuously and monotonically decreases in the gradient compatibility buffer transition layer.

[0042] The gradient compatibility buffer transition layer does not have a layered interface formed by the solidification of at least three semi-conductive polyolefin-based composite melts, and the gradient compatibility buffer transition layer and the insulating layer, as well as the gradient compatibility buffer transition layer and the insulating shielding layer, are all direct fusion bonding interfaces.

[0043] S1. Provide a conductor and extrude a conductor shielding layer outside the conductor;

[0044] S2. Using a split-feed co-extrusion process, an insulating layer, a gradient compatibility buffer transition layer, and an insulating shield layer are integrally formed outside the conductor shield layer. At least three semi-conductive polyolefin-based composite melts forming the gradient compatibility buffer transition layer are fed into the converging composite zone through at least three independent flow channels in the co-extrusion die head, and are melted and composited in a radial order from the side closest to the insulating layer to the side closest to the insulating shield layer.

[0045] The content of compatible components in at least three semiconductive polyolefin-based composite melts decreases in radial order, while the content of conductive fillers increases in radial order.

[0046] The temperature of each independent flow channel and the feed flow rate of each stream of semiconductive polyolefin-based composite melt are set differently according to radial order.

[0047] S3. Perform cross-linking treatment on the cable core obtained in step S2;

[0048] S4. Perform segmented cooling treatment on the cable core after cross-linking treatment in step S3. The segmented cooling treatment includes a first stage cooling and a second stage cooling. The first stage cooling is a stress relief and slow cooling stage, and the second stage cooling is a rapid shaping cooling stage. The cooling rate of the first stage is lower than that of the second stage cooling.

[0049] The first stage of cooling is used to reduce the radial shrinkage difference of the cross-linked cable core and the concentration of interfacial thermal stress, while the second stage of cooling is used to quickly shape the continuous gradient distribution and fusion bonding interface after the interfacial thermal stress is relieved.

[0050] S5. The cable core after step S4 is degassed, and a metal shielding layer, an inner lining layer, an armor layer and an outer sheath layer are formed sequentially on the outside of the degassed cable core.

[0051] This embodiment uses a 110 kV medium-high voltage cable as an example for illustration.

[0052] The conductor is a Class 2 annealed copper conductor conforming to GB / T 3956 standard, with a nominal cross-sectional area of ​​630 mm². 2 The conductor shielding layer is made of cross-linkable semi-conductive shielding material and is formed by single-screw extrusion process. The insulation layer is made of cross-linkable polyethylene insulation material, and the insulation shielding layer is made of cross-linkable semi-conductive shielding material. A gradient compatibility buffer transition layer is set between the insulation layer and the insulation shielding layer, with a thickness of 0.08 mm.

[0053] The semi-conductive polyolefin-based composite material used in the gradient compatibility buffer transition layer comprises, by weight, 65 parts of polyolefin matrix, 25 parts of conductive filler, and 10 parts of compatibility component; wherein, the polyolefin matrix is ​​formed by blending low-density polyethylene and linear low-density polyethylene in a weight ratio of 6:4; the conductive filler is acetylene black; the compatibility component consists of 8 parts of polyethylene grafted with maleic anhydride and 2 parts of nano-silica modified with silane coupling agent KH-550, the nano-silica having a particle size of 20-30 nm.

[0054] To form a gradient compatibility buffer transition layer, three types of semiconductive masterbatches were prepared in advance. Masterbatch A is a high compatibility component masterbatch near the insulating layer, with the total content of the compatibility component increased to 15 wt% based on the above basic formulation; Masterbatch B is an intermediate masterbatch with a compatibility component content of 8 wt%; Masterbatch C is a low compatibility component masterbatch near the insulating shielding layer with a compatibility component content of 2 wt%.

[0055] After each component is premixed separately, they are melt-blended and granulated in a twin-screw extruder to obtain three types of masterbatches.

[0056] Medium and high voltage cables are manufactured using the following methods:

[0057] The first step is conductor preparation, which involves providing a Class 2 annealed copper conductor.

[0058] The second step is the formation of the conductor shielding layer. A cross-linkable semi-conductive shielding material is extruded from the outside of the conductor using a single-screw extruder to form the conductor shielding layer.

[0059] The third step is the formation of an insulating composite structure.

[0060] Using a split-feed co-extrusion process, an insulating layer, a gradient compatibility buffer transition layer, and an insulating shielding layer are integrally formed outside the conductor shielding layer.

[0061] Specifically, the insulating layer is formed by extrusion using a corresponding insulating extruder, the insulating shielding layer is formed by extrusion using a corresponding semi-conductive shielding layer extruder, and the gradient compatibility buffer transition layer is formed by melt supplied to masterbatch A, masterbatch B, and masterbatch C by three independent extruders respectively. Masterbatch A, masterbatch B, and masterbatch C all use the same polyolefin matrix system composed of low-density polyethylene and linear low-density polyethylene, the difference being the content of compatibility components and conductive fillers; among them, masterbatch A corresponds to the side closer to the insulating layer, masterbatch B corresponds to the middle position in the thickness direction, and masterbatch C corresponds to the side closer to the insulating shielding layer.

[0062] Three independent extruders plasticize masterbatch A, masterbatch B, and masterbatch C into a first melt, a second melt, and a third melt, respectively, and feed them into three independent annular flow channels in the composite die head. The three independent annular flow channels are arranged in sequence along the radial direction of the cable core, and the outlets of the three independent annular flow channels are connected to the same annular confluence composite area. The first melt is located near the insulation layer, the second melt is located in the middle, and the third melt is located near the insulation shielding layer, so that the three melts are arranged in radial order before entering the thin-walled forming gap between the insulation layer and the insulation shielding layer.

[0063] During co-extrusion, the temperature of the independent flow channel near the insulation layer is set to 113℃, the temperature of the middle independent flow channel is set to 110℃, the temperature of the independent flow channel near the insulation shielding layer is set to 107℃, the temperature of the composite die head is set to 105~110℃, the melt pressure is controlled to 22~28MPa, and the traction speed is controlled to 9.5~10m / min. By adjusting the screw speed of the three independent extruders, the first melt, the second melt, and the third melt are kept continuously and stably fed in the confluence and composite zone, and the shear rate ratio of the three melts is controlled to be 1.0:1.2:1.5.

[0064] Since the first, second, and third melts use the same polyolefin matrix system, and the differences in the content of compatible components and conductive fillers between adjacent melts are set progressively, the three melts are in a molten contact state within the confluence and composite zone. Through the independent flow channel temperature decrease, the shear rate increase, and the feeding state matching, the adjacent melts undergo controlled molten composite and interface widening within the confluence and composite zone, rather than forming independent cold stacks. As a result, a molten composite region with gradually transitioning composition is formed between the first and second melts and between the second and third melts, thereby obtaining a gradient compatibility buffer transition layer with a thickness of 0.08 mm located between the insulating layer and the insulating shielding layer.

[0065] Crosslinking and post-treatment: The extruded cable core is immediately fed into a catenary crosslinking tube for peroxide vapor crosslinking at a temperature of 170°C and a pressure of 1.2 MPa. After crosslinking, a segmented cooling process is performed, consisting of a first-stage cooling and a second-stage cooling. The first-stage cooling is a stress-relieving slow cooling stage, in which circulating hot water or warm water is used to cool the cable core to 118–130°C at a rate of 0.5–1.2°C / s (120°C in this embodiment). This is used to reduce the radial shrinkage difference and interfacial thermal stress concentration of the crosslinked cable core, and to avoid interfacial disturbance between the gradient compatibility buffer transition layer and the insulation layer and insulation shielding layer due to rapid cooling. The second-stage cooling is a rapid shaping cooling stage, in which room temperature water spray or water tank cooling is used to cool the cable core to room temperature at a rate of 2.5–5.0°C / s. This is used to shape the gradient compatibility buffer transition layer and its fusion bonding interface after the interfacial thermal stress is relieved. Subsequently, vacuum degassing is performed at 75°C for 48 hours.

[0066] The sheathing is formed by sequentially forming a copper wire loose-wound metal shielding layer, a PVC inner lining layer, a galvanized steel tape armor layer, and an HDPE outer sheath layer on the outside of the cable core after cross-linking, segmented cooling, and degassing treatment, resulting in a finished medium and high voltage cable.

[0067] Furthermore, to confirm that the obtained transition layer is not a simple stacked structure of three layers, a continuous line scan characterization was performed on the cross-section of the gradient compatibility buffer transition layer. The scan path was set along the thickness direction of the gradient compatibility buffer transition layer, and passed sequentially through the side near the insulating layer, the middle position in the thickness direction, and the side near the insulating shielding layer. In the scan results, the intensity of the carbonyl characteristic peak and the silicon-oxygen bond characteristic peak did not show a step-like abrupt change, but rather showed a continuous decreasing curve along the thickness direction. Correspondingly, when the micro-resistivity test was used to measure point by point along the thickness direction, the volume resistivity decreased continuously from the side near the insulating layer to the side near the insulating shielding layer, and no abrupt plateau appeared between adjacent layers. Combined with the scanning electron microscope observation results, it can be seen that no penetrating abrupt delamination interface, air gap, or debonding region was observed inside the gradient compatibility buffer transition layer, indicating that the three melts formed a continuous molten composite structure in the confluence composite region, rather than forming an independent three-layer stepped structure.

[0068] To verify the technical effect of this embodiment, the cable sample was subjected to performance testing under actual operating conditions. The specific test conditions were as follows: the conductor was subjected to the rated load current to form a radial temperature gradient, wherein the temperature on the conductor side was about 70°C and the temperature on the outer side was about 40°C; a DC voltage gradient of 8 kV / mm was applied to the sample and it was aged for 1000 h; after aging, the space charge distribution was measured by pulse electroacoustic method, and the electric field distortion rate and interface peel strength were tested.

[0069] For comparison, the following comparative samples were prepared strictly according to the same basic materials and process specifications:

[0070] Comparative Example 1: Without a gradient compatibility buffer transition layer, the insulation layer and the insulation shielding layer are directly co-extruded to form a traditional structure cable;

[0071] Comparative Example 2: A uniform semiconductive transition layer was formed, and the content of the compatible component was kept constant at 8 wt%;

[0072] Comparative Example 3: Three stepped transition layers were set up, with the contents of the compatible components in the three layers being 15 wt%, 8 wt%, and 2 wt%, respectively, forming abrupt interfaces between the layers;

[0073] Comparative Example 4: A uniform transition layer was set up, the compatible component of which was only 10 wt% grafted maleic anhydride polyethylene, without surface-modified nano silica.

[0074] The test results for each sample are shown in Table 1.

[0075] Table 1 Comparison of performance test results for different cable structures

[0076] sample Transition layer structure description Distribution characteristics of compatible components Maximum space charge density (C / m³) Electric field distortion rate (%) Interfacial peel strength (N / cm) Example 1 Gradient Compatibility Buffer Transition Layer 15 wt% → 2 wt% (continuously decreasing) 1.8 12 28 Comparative Example 1 No transition layer (direct co-extrusion) none 4.2 35 15 Comparative Example 2 Uniform semiconductive transition layer constant 8 wt% 3.5 28 19 Comparative Example 3 Three-tiered transition layer 15 / 8 / 2 wt% (step mutation) 2.9 22 22 Comparative Example 4 Uniform transition layer with single compatibilizer Constant 10 wt% (PE-g-MAH only) 3.1 25 21

[0077] As shown in Table 1, compared with Comparative Example 1, this embodiment shows significant improvements in the three indicators of maximum space charge density, electric field distortion rate, and interface peel strength. This indicates that setting a gradient compatibility buffer transition layer between the insulating layer and the insulating shielding layer is beneficial to reducing space charge accumulation at the interface and improving the interface bonding performance. Compared with Comparative Examples 2 and 4, this embodiment not only introduces a gradient distribution, but also makes the performance transition of the transition layer in the thickness direction smoother through the synergistic effect of grafted maleic anhydride polyethylene and surface-modified nano-silica. Compared with Comparative Example 3, this embodiment adopts a continuously decreasing gradient structure instead of a step-change structure, which further improves the space charge suppression effect and interface bonding performance.

[0078] In summary, this embodiment constructs a gradient compatible buffer transition layer with continuously decreasing compatible components through a split-feed co-extrusion process, and retains this gradient structure and the direct fusion bonding interface between it and adjacent layers through a segmented cooling process after cross-linking. This achieves the suppression of space charge accumulation, the reduction of electric field distortion, and the improvement of interface bonding strength.

[0079] Example 2

[0080] This is a second embodiment of the present invention, which provides a medium- and high-voltage cable, comprising:

[0081] The thickness of the gradient compatibility buffer transition layer is 0.05–0.12 mm;

[0082] By weight, the semi-conductive polyolefin-based composite material comprises 55-75 parts of polyolefin matrix, 20-30 parts of conductive filler and 6-12 parts of compatible component;

[0083] The compatible components include 5-10 parts grafted maleic anhydride polyethylene and 1-3 parts surface-modified nano silica;

[0084] The polyolefin matrix includes low-density polyethylene and linear low-density polyethylene, and the mass ratio of low-density polyethylene to linear low-density polyethylene is 6:4 to 7:3; the conductive filler is acetylene black.

[0085] The particle size of the surface-modified nano-silica is 20–30 nm. The modification method is plasma treatment or silane coupling agent modification, and the surface roughness after modification is 30–60 nm.

[0086] Along the thickness direction of the gradient compatibility buffer transition layer, select the first detection position near the insulating layer, the second detection position in the middle of the thickness direction, and the third detection position near the insulating shielding layer.

[0087] The content of the compatible component at the first detection position is higher than that at the second detection position, and the content of the compatible component at the second detection position is higher than that at the third detection position.

[0088] The conductive filler content at the first detection position is lower than that at the second detection position, and the conductive filler content at the second detection position is lower than that at the third detection position.

[0089] Among them, the first detection position, the second detection position and the third detection position represent the continuous gradient change of the gradient compatibility buffer transition layer along the thickness direction, and do not constitute an independent layered structure.

[0090] The volume resistivity of the gradient compatibility buffer transition layer near the insulating layer is 8.0 × 10⁻⁶. 4 ~1.3×10 5 The volume resistivity of the gradient compatibility buffer transition layer near the insulating shielding layer is 8.0 × 10 Ω·cm. 2 ~2.0×10 3 Ω·cm.

[0091] This embodiment illustrates that when the thickness of the gradient compatibility buffer transition layer, the formulation of the semi-conductive polyolefin-based composite material, the composition of the compatibility components, and the volume resistivity distribution along the thickness direction are within the limits defined by this invention, a medium- and high-voltage cable with a continuous transition interface can be obtained, and the accumulation of space charge and electric field distortion at the interface can be effectively reduced.

[0092] This embodiment uses a 110 kV medium-high voltage cable as an example for illustration.

[0093] The cable comprises, from the inside out, a conductor, a conductor shielding layer, an insulation layer, a gradient compatibility buffer transition layer, an insulation shielding layer, a metal shielding layer, an inner liner, an armor layer, and an outer sheath layer. The gradient compatibility buffer transition layer is disposed between the insulation layer and the insulation shielding layer and is made of a semi-conductive polyolefin-based composite material.

[0094] The semi-conductive polyolefin-based composite material comprises, by weight, 68 parts of polyolefin matrix, 24 parts of conductive filler, and 8 parts of compatible component.

[0095] The polyolefin matrix is ​​composed of a blend of low-density polyethylene and linear low-density polyethylene in a weight ratio of 7:3; the conductive filler is acetylene black; the compatible components include 6.5 parts of maleic anhydride-grafted polyethylene and 1.5 parts of surface-modified nano-silica.

[0096] Surface-modified nano-silica was obtained by modification with silane coupling agent KH-550, and its original particle size was 25 nm.

[0097] The specific modification process is as follows: Nano-silica powder is dispersed in anhydrous ethanol to form a suspension. KH-550 is added under mechanical stirring, and the pH of the system is adjusted to 4-5 with acetic acid. The reaction is carried out at 60°C, followed by centrifugation, ethanol washing, and vacuum drying to obtain surface-modified nano-silica. The surface roughness of the modified particles is approximately 45 nm. Preferably, the surface roughness is measured using an atomic force microscope.

[0098] The conductor is a Class 2 annealed copper conductor with a nominal cross-sectional area of ​​630 mm². The conductor shielding layer is disposed on the outside of the conductor. The insulation layer is formed of cross-linkable polyethylene insulation material. The insulation shielding layer is disposed on the outside of the gradient compatibility buffer transition layer. The thickness of the gradient compatibility buffer transition layer is 0.08 mm, which is within the thickness range of 0.02 to 0.50 mm defined in this invention.

[0099] To ensure a continuously decreasing volume resistivity along the thickness direction of the gradient compatibility buffer transition layer, three masterbatches for forming the layer are prepared in advance. Masterbatch G is used to form the region near the insulating layer, with a conductive filler content of 20 parts and a compatibility component content of 12 parts. Masterbatch H is used to form the intermediate region, with a conductive filler content of 24 parts and a compatibility component content of 8 parts. Masterbatch I is used to form the region near the insulating shielding layer, with a conductive filler content of 28 parts and a compatibility component content of 4 parts. Through these settings, the compatibility component content gradually decreases and the conductive filler content gradually increases along the thickness direction of the gradient compatibility buffer transition layer from the side near the insulating layer to the side near the insulating shielding layer, thereby achieving a continuous decrease in volume resistivity.

[0100] The cable is manufactured using a three-layer co-extrusion process with separate feed. Three masterbatch melts enter the composite die head through three independent channels and are melted and composited in the confluence composite zone of the composite die head in a radial order from the side closest to the insulation layer to the side closest to the insulation shielding layer. This forms a gradient compatibility buffer transition layer between the insulation layer and the insulation shielding layer. During the co-extrusion process, by controlling the temperature, melt pressure, feed flow rate of each melt strand, and traction speed in each independent channel, the content of compatible components decreases along the thickness direction of the gradient compatibility buffer transition layer, and the volume resistivity decreases from a higher value near the insulation layer to a lower value near the insulation shielding layer.

[0101] In this embodiment, the key co-extrusion process parameters are as follows: the extruder temperature range for the insulating layer is 110-115-115-110℃, the extruder temperature range for the transition layer is 105-110-110-105℃, the extruder temperature range for the insulating shielding layer is 100-105-105-100℃, the composite die head temperature is 108℃, and the traction speed is 10.5 m / min.

[0102] The co-extruded cable core is immediately fed into a CCV cross-linking tube for peroxide vapor cross-linking at a temperature of 172°C and a pressure of 1.25 MPa. Subsequently, it undergoes segmented cooling: in the first stage, it is slowly cooled to 125°C at a rate of 0.8°C / s, and in the second stage, it is rapidly cooled to room temperature at a rate of 3.2°C / s. Afterward, it is vacuum degassed at 75°C for 48 hours. Finally, a metal shielding layer, an inner lining layer, an armor layer, and an outer sheath layer are sequentially formed on the outside of the cable core to obtain the finished cable.

[0103] The measured thickness of the gradient compatibility buffer transition layer in the cable produced by the above process is 0.08 mm.

[0104] Scanning electron microscopy revealed that the interface between the gradient compatibility buffer transition layer and the insulating layer and insulating shielding layer was well fused, with no visible air gaps or delamination, forming a continuous fused interface.

[0105] Using a microresistivity meter, point-by-point scanning was performed along the thickness direction of the gradient compatibility buffer transition layer. The results showed that the volume resistivity decreased from approximately 1.1 × 10⁻⁶ near the insulating layer. 5 The Ω·cm decreases smoothly and continuously to approximately 9.0 × 10⁻⁶ near the insulating shielding layer. 2 The Ω·cm indicates that this embodiment not only forms a gradient-compatible buffer transition layer, but also achieves a continuous resistivity gradient along the thickness direction.

[0106] To verify the technical effect of this embodiment, a 110 kV-level cable sample was prepared for performance testing. The test conditions were as follows: a rated load current was applied to the conductor to form a radial temperature gradient, wherein the temperature on the conductor side was about 72°C and the temperature on the outer side was about 38°C; a DC voltage gradient of 8.5 kV / mm was applied to the sample and it was aged for 1200 h; after aging, the space charge distribution was measured by pulse electroacoustic method and the electric field distortion rate was calculated.

[0107] For comparison, the following comparative samples were prepared using the same basic materials and process specifications:

[0108] Comparative Example 1: Without a gradient compatibility buffer transition layer, the insulation layer and the insulation shielding layer are directly co-extruded to form a traditional structure cable;

[0109] Comparative Example 2: A transition layer with continuously decreasing volume resistivity is set, but the thickness of the transition layer is 0.60 mm;

[0110] Comparative Example 3: A transition layer with a thickness of 0.08 mm was set, but its volume resistivity remained constant along the thickness direction;

[0111] Comparative Example 4: A transition layer with a thickness of 0.08 mm and a continuously decreasing volume resistivity was set, but the nano-silica in it was not surface modified;

[0112] Comparative Example 5: A transition layer with continuously decreasing volume resistivity is set, but the thickness of the transition layer is 0.01 mm.

[0113] The performance test results of each sample are shown in Table 2.

[0114] Table 2. Impact of different transition layer designs on cable performance

[0115] sample Transition layer thickness (mm) Resistivity distribution characteristics <![CDATA[Nano SiO2 modification]]> <![CDATA[Maximum space charge density (C / m 3 )]]> Electric field distortion rate (%) Example 2 of this invention 0.08 continuous decrease Yes (roughness 45 nm) 1.6 11 Comparative Example 1 none mutation - 4.5 37 Comparative Example 2 0.60 continuous decrease yes 3.2 26 Comparative Example 3 0.08 constant yes 3.4 29 Comparative Example 4 0.08 continuous decrease no 2.7 21 Comparative Example 5 0.01 continuous decrease yes 3.8 32

[0116] As shown in Table 2, the maximum space charge density of Example 2 is 1.6 C / m³, and the electric field distortion rate is 11%, which are the best among all samples. Compared with Comparative Example 1, this example significantly reduces the accumulation of space charge at the interface and significantly reduces electric field distortion after setting a gradient compatibility buffer transition layer with continuously decreasing volume resistivity between the insulating layer and the insulating shielding layer. Compared with Comparative Example 2, it shows that an excessively thick transition layer cannot further optimize the electrical performance. Compared with Comparative Example 3, it shows that having only a transition layer thickness without a continuously decreasing volume resistivity distribution along the thickness direction cannot achieve the electrical improvement effect of the present invention. Compared with Comparative Example 4, it shows that surface-modified nano-silica helps maintain interface compatibility and improve the electric field distribution. Compared with Comparative Example 5, it shows that an excessively thin transition layer is difficult to form a sufficiently effective continuous gradient buffer effect.

[0117] In summary, this embodiment controls the thickness of the gradient compatibility buffer transition layer within the limits defined by this invention, and makes it form a continuously decreasing volume resistivity distribution along the thickness direction. At the same time, it uses surface-modified nano-silica to enhance the interfacial compatibility between the compatibility component and the polyolefin matrix and conductive filler, thereby obtaining a gradient compatibility buffer transition layer with a continuous fused bonding interface between the insulating layer and the insulating shielding layer. This structure can effectively suppress space charge accumulation and reduce electric field distortion.

[0118] Example 3

[0119] This is a third embodiment of the present invention, which provides a method for preparing a medium- and high-voltage cable, comprising the following steps:

[0120] In step S2, in each strand of semiconductive polyolefin-based composite melt entering different independent flow channels, the content of compatible components decreases in radial order, while the content of conductive filler increases in radial order.

[0121] In step S2, the temperature of the independent flow channel near the insulating layer is 111-115°C, the temperature of the middle independent flow channel is 108-112°C, and the temperature of the independent flow channel near the insulating shielding layer is 105-109°C.

[0122] The co-extrusion die head temperature is 108–112℃, the melt pressure is 22–28MPa, and the traction speed is 9–11m / min;

[0123] The shear rate ratio of the first melt, the second melt, and the third melt is 1.0:1.1~1.3:1.4~1.6;

[0124] In step S4, the first stage of cooling uses circulating hot water for slow cooling, reducing the cross-linked cable core to 118-130°C at a cooling rate of 0.5-1.2°C / s;

[0125] The second stage of cooling uses ambient temperature water spraying or water tank cooling to cool the cable core, which has been cooled in the first stage, to room temperature at a cooling rate of 2.5 to 5.0℃ / s.

[0126] This embodiment illustrates that by constructing a gradient compatibility buffer transition layer using a branched feeding co-extrusion process, and maintaining the continuous decreasing structure and continuous fusion bonding interface of the gradient compatibility buffer transition layer through segmented cooling treatment after cross-linking, a medium- and high-voltage cable with excellent electrical performance and interface bonding performance can be obtained.

[0127] This embodiment uses the preparation method of a 110 kV medium-high voltage cable as an example for illustration.

[0128] The preparation method includes the following steps.

[0129] S1, Formation of conductor and conductor shielding layer

[0130] Provide a Class 2 annealed copper conductor with a nominal cross-sectional area of ​​630 mm², and extrude a cross-linkable semiconductive shielding material onto the conductor using a single-screw extruder to form a conductor shielding layer;

[0131] S2, Formation of insulating composite structure

[0132] An insulating layer, a gradient compatibility buffer transition layer, and an insulating shielding layer are integrally formed outside the conductor shielding layer using a split-feed co-extrusion process.

[0133] The insulating layer is formed of cross-linkable polyethylene insulating material, the insulating shielding layer is formed of cross-linkable semi-conductive shielding material, and the gradient compatibility buffer transition layer is formed of semi-conductive polyolefin-based composite material. The semi-conductive polyolefin-based composite material includes a polyolefin matrix, conductive filler and compatibility components. The compatibility components include maleic anhydride-grafted polyolefin and / or surface-modified nano-silica.

[0134] To achieve a continuous decrease in the content of the compatible component along the thickness direction of the gradient compatible buffer transition layer, three semi-conductive polyolefin-based composite melts with different contents of compatible components were prepared in advance and introduced into three independent flow channels of the co-extrusion die head. Among the three melts, the first melt near the insulating layer had the highest content of compatible components, the second melt in the middle had the second highest content of compatible components, and the third melt near the insulating shielding layer had the lowest content of compatible components.

[0135] Specifically, in this embodiment, the contents of the compatible components of the three melts are 13 wt%, 6.5 wt%, and 1.8 wt%, respectively.

[0136] After the three melt streams are fed into the three independent annular channels of the composite die head, they enter the same annular confluence composite zone and melt composite in a radial sequence: the side closest to the insulation layer, the middle position, and the side closest to the insulation shielding layer. The temperature of the channel closest to the insulation layer is set to 113℃, the temperature of the middle channel is set to 110℃, and the temperature of the channel closest to the insulation shielding layer is set to 107℃. The feeding state of each melt stream is controlled by adjusting the screw speed of the three extruders, so that the shear rate ratio of the three melt streams is approximately 1.0:1.2:1.5. Since the three melt streams use the same polyolefin matrix system and the component content varies, the three melt streams undergo controlled melting composite and interface broadening in the confluence composite zone, thereby forming a gradient compatibility buffer transition layer with a thickness of 0.08mm.

[0137] The key process parameters for co-extrusion are as follows: the temperature range of the first extruder is 115-120-120-115℃, the temperature of the relevant flow channels in the transition layer is 112-108℃, the temperature range of the third extruder is 105-110-110-105℃, the temperature of the composite die head is 110℃, the melt pressure is 22~28 MPa, and the traction speed is 9.5 m / min.

[0138] S3, crosslinking and segmented cooling treatment

[0139] The cable core obtained in step S2 is immediately subjected to peroxide vapor crosslinking treatment.

[0140] The cross-linking temperature is 172℃ and the cross-linking pressure is 1.25 MPa. After cross-linking, the cable core is subjected to segmented cooling treatment. In the first stage, circulating hot water is used for slow cooling to gradually reduce the cable core temperature to 125℃. In the second stage, room temperature water spray is used for shaping and cooling to cool the cable core to room temperature.

[0141] In this embodiment, the cooling rate in the first stage is controlled at 0.8 ℃ / s, and the cooling rate in the second stage is controlled at 3.2 ℃ / s. The first stage cooling uses circulating hot water for slow cooling to gradually reduce the core temperature to 125 ℃, which is used to reduce the radial shrinkage difference of the core after cross-linking and the concentration of interfacial thermal stress, and to avoid interfacial disturbance between the gradient compatibility buffer transition layer and the insulation layer and the insulation shielding layer due to rapid cooling. The second stage cooling uses room temperature water spray for rapid shaping to cool the core to room temperature, which is used to shape the gradient compatibility buffer transition layer and its fusion bonding interface after the interfacial thermal stress is relieved.

[0142] S4, Degassing and Cover Formation

[0143] After step S3, the cable core is subjected to vacuum degassing at 75°C for 48 hours to remove residual cross-linking byproducts. A copper wire loose-wound metal shielding layer, a PVC inner lining layer, a galvanized steel tape armor layer, and a high-density polyethylene outer sheath layer are formed sequentially on the outside of the cable core to obtain the finished medium and high voltage cable.

[0144] The cable prepared according to the method of this embodiment is structurally represented. Observation by scanning electron microscopy shows that the interface between the gradient compatibility buffer transition layer and the insulation layer and the insulation shielding layer is continuous, with no visible air gaps or delamination, forming a continuous fused bonding interface.

[0145] Further analysis of the microresistivity scanning results from Example 2 reveals that the gradient compatibility buffer transition layer prepared using the method of this example can achieve a continuous decrease in volume resistivity from the side closer to the insulating layer to the side closer to the insulating shielding layer.

[0146] To verify the technical effectiveness of the preparation method in this embodiment, a 110 kV-level cable sample was prepared and tested under seasonal load operation scenarios of urban underground power grids.

[0147] The test conditions are as follows: A rated load current is applied to the conductor to form a radial temperature gradient, with the conductor side temperature being approximately 70–73°C and the outer side temperature being approximately 37–41°C; a DC voltage gradient of 8.5 kV / mm is applied to the sample, and aging is continued for 1200 h; after aging, the space charge distribution is measured using the pulsed electroacoustic method, and the electric field distortion rate, interface peel strength, and breakdown voltage after aging are tested.

[0148] For comparison, the following comparative samples were prepared using the same basic materials and main process specifications:

[0149] Comparative Example 1: After cross-linking, a single rapid cooling process was used, without segmented cooling;

[0150] Comparative Example 2: A segmented cooling process was adopted, but the rate difference between the first stage cooling and the second stage cooling was small;

[0151] Comparative Example 3: When forming a gradient compatible buffer transition layer, only the difference in the content of compatible components is controlled, and the temperature difference of independent flow channels and the difference in melt shear rate ratio are not set.

[0152] Comparative Example 4: When forming a gradient compatible buffer transition layer, the temperature difference, shear rate ratio and compatibility component content difference are set simultaneously, but the control is insufficient, resulting in poor stability of the gradient structure.

[0153] The performance test results of each sample are shown in Table 3.

[0154] Table 3. Effects of different cooling and gradient control processes on cable performance

[0155] Sample number Key process features <![CDATA[Maximum space charge density (C / m 3 )]]> Electric field distortion rate (%) Interfacial peel strength (N / cm) Breakdown voltage after aging (kV) Example 3 Segmented cooling (significantly different cooling rates) + multi-parameter gradient control 1.65 11.5 27.8 187 Comparative Example 1 Single rapid cooling 3.05 25 20.5 164 Comparative Example 2 Segmented cooling, but with small differences in cooling rates. 2.45 19.5 23 171 Comparative Example 3 Content difference control only (no temperature difference or shear rate ratio) 2.70 22 21.5 168 Comparative Example 4 Insufficient multi-parameter control 2.85 23.5 19.8 162

[0156] As shown in Table 3, the cable prepared in Example 3 outperforms the comparative examples in all four indicators: maximum space charge density, electric field distortion rate, interfacial peel strength, and breakdown voltage after aging. Compared with Comparative Example 1, it shows that segmented cooling instead of single rapid cooling after crosslinking is beneficial for suppressing space charge accumulation, reducing electric field distortion, and improving interfacial bonding performance. Compared with Comparative Example 2, it shows that maintaining a significant rate difference between the first stage of slow cooling and the second stage of shaping cooling, and maintaining the radial temperature gradient between the cable core and the cooling medium during the cooling process, is beneficial for further stabilizing the structure of the gradient compatibility buffer transition layer. Compared with Comparative Example 3, it shows that relying solely on the difference in compatibility component content without coordinating the temperature difference of independent flow channels and the melt shear rate ratio makes it difficult to form a stable, continuously decreasing gradient structure. Compared with Comparative Example 4, it shows that even if multiple control factors are used simultaneously, if the degree of control is insufficient, it is difficult to obtain structural stability and comprehensive performance comparable to that of this example.

[0157] In summary, this embodiment achieves a continuously decreasing gradient structure in the gradient compatibility buffer transition layer during co-extrusion by co-controlling the differences in the content of compatible components, the temperature difference of independent flow channels, the melt flow state, and the supply ratio. Furthermore, after cross-linking, segmented cooling and radial temperature gradient maintenance ensure that this gradient structure is stably retained during subsequent manufacturing processes. This results in a medium- and high-voltage cable with a continuous molten bonding interface, low space charge density, low electric field distortion rate, high interfacial peel strength, and high breakdown voltage after aging.

[0158] Example 4

[0159] This is the fourth embodiment of the present invention. This embodiment provides a medium- and high-voltage cable and a method for manufacturing the same, comprising:

[0160] The polyolefin matrix includes low-density polyethylene and linear low-density polyethylene, and the mass ratio of low-density polyethylene to linear low-density polyethylene is 6:4 to 7:3; the conductive filler is acetylene black.

[0161] The particle size of the surface-modified nano-silica is 20–30 nm. The modification method is plasma treatment or silane coupling agent modification, and the surface roughness after modification is 30–60 nm.

[0162] Step S3 uses peroxide vapor crosslinking; step S5 uses vacuum degassing.

[0163] The metal shielding layer is a loosely wound copper wire metal shielding layer, the inner lining layer is a PVC inner lining layer, the armor layer is a galvanized steel strip armor layer, and the outer sheath layer is a high-density polyethylene outer sheath layer.

[0164] This embodiment is used to further explain the key process control points in the preparation method of the present invention, especially to refine and disclose the multi-parameter synergistic control in the gradient compatibility buffer transition layer formation stage and the gradient maintenance conditions in the segmented cooling stage after crosslinking, so as to enhance the feasibility and repeatability of the preparation method of the present invention.

[0165] This embodiment uses the preparation method of a 110 kV medium-high voltage cable as an example for illustration.

[0166] The prepared medium and high voltage cable includes, from the inside out, a conductor, a conductor shielding layer, an insulation layer, a gradient compatibility buffer transition layer, an insulation shielding layer, a metal shielding layer, an inner lining layer, an armor layer, and an outer sheath layer. The gradient compatibility buffer transition layer is disposed between the insulation layer and the insulation shielding layer and is formed of a semi-conductive polyolefin-based composite material.

[0167] Based on Example 3, this embodiment specifically implements the key process control points involved in steps S2 and S3. The basic formulation of the semi-conductive polyolefin-based composite material used in the gradient compatibility buffer transition layer can be the same as that in Example 3.

[0168] S1, Formation of conductor and conductor shielding layer.

[0169] A type 2 annealed copper conductor is provided, and a conductor shielding layer is formed on the outside of the conductor by an extrusion process to obtain a base cable core for subsequent insulation composite structure formation.

[0170] S2, precise formation of gradient compatible buffer transition layer.

[0171] A split-feed co-extrusion process is adopted to integrally form an insulating layer, a gradient compatibility buffer transition layer, and an insulating shielding layer outside the conductor shielding layer. In order to achieve a stable and continuously decreasing structure, three semi-conductive polyolefin-based composite material melts with different compatibility component contents are pre-prepared. The compatibility component contents in the three melts are 13 wt%, 6.5 wt%, and 1.8 wt%, respectively. The melt with the highest compatibility component content is used to form the region near the insulating layer, and the melt with the lowest compatibility component content is used to form the region near the insulating shielding layer.

[0172] Three melt streams are fed into three independent channels of the composite die head. By coordinating the control of the temperature, melt shear rate ratio, and compatibility component content difference in each independent channel, the three melt streams form a stable radial laminar superposition within the composite die head.

[0173] Specifically, the flow channel temperature near the insulation layer is set to 113°C, the middle flow channel temperature is set to 110°C, and the flow channel temperature near the insulation shielding layer is set to 107°C; by adjusting the screw speeds of the three extruders, the shear rate ratio of the three melts is made to be approximately 1.0:1.2:1.5.

[0174] By controlling the flow channel temperature, screw speed, feed flow rate, and shear rate ratio, the three melt streams are melted and compounded in a radial sequence within the confluence and compounding zone of the compounding die head, resulting in a gradient compatibility buffer transition layer with a thickness of 0.08 mm. Subsequent micro-infrared spectroscopy line scanning and micro-resistivity testing verified that the content of the compatibility component in this gradient compatibility buffer transition layer decreases along its thickness direction from the side closer to the insulating layer to the side closer to the insulating shielding layer, while the volume resistivity decreases along the same direction.

[0175] In this embodiment, the gradient compatibility buffer transition layer forms a continuous fusion bonding interface with the insulating layer and the insulating shielding layer during its formation.

[0176] S3, cross-linking and segmented cooling treatment.

[0177] After completing step S2, the extruded cable core is immediately subjected to peroxide vapor crosslinking treatment at a crosslinking temperature of 172°C and a crosslinking pressure of 1.25 MPa.

[0178] After cross-linking is completed, segmented cooling treatment is carried out. In the first stage, circulating hot water is used for slow cooling to gradually reduce the core temperature to 125°C. In the second stage, room temperature water spray is used for shaping and cooling to quickly cool the core to room temperature.

[0179] In this embodiment, the cooling rate in the first stage is controlled at 0.8 ℃ / s, and the cooling rate in the second stage is controlled at 3.2 ℃ / s. During the segmented cooling process, the radial temperature gradient between the cable core and the cooling medium is maintained. By performing slow cooling first after cross-linking and then shaping cooling, and maintaining the radial temperature gradient during the cooling process, the risk of diffusion and gradient blurring of components in the gradient compatibility buffer transition layer after high-temperature cross-linking can be reduced. At the same time, the thermal stress difference between different component materials can be alleviated, thereby maintaining a continuously decreasing gradient structure and ensuring the continuity of interface fusion bonding.

[0180] S4, Degassing and Protective Layer Formation.

[0181] After the cable core is processed in step S3, it undergoes vacuum degassing at a temperature of 75°C for 48 hours. After degassing, a metal shielding layer, an inner lining layer, an armor layer, and an outer sheath layer are formed sequentially on the outside of the cable core.

[0182] Preferably, the metal shielding layer is a loosely wound copper wire metal shielding layer, the inner lining layer is a PVC inner lining layer, the armor layer is a galvanized steel strip armor layer, and the outer sheath layer is a high-density polyethylene outer sheath layer.

[0183] When the key process control parameters of this embodiment are used for preparation, a gradient compatibility buffer transition layer with a thickness of 0.08 mm can be stably formed. The content of the compatibility component in the transition layer decreases continuously along the thickness direction and forms a continuous molten bonding interface with the insulating layer and the insulating shielding layer. This embodiment is used to further specify the key process control points in the preparation method of Example 3.

Claims

1. A medium- and high-voltage cable, characterized in that, It includes, from the inside out, a conductor, a conductor shielding layer, an insulation layer, a gradient compatibility buffer transition layer, an insulation shielding layer, a metal shielding layer, an inner liner, an armor layer, and an outer sheath layer; The gradient compatibility buffer transition layer is disposed between the insulating layer and the insulating shielding layer, and the gradient compatibility buffer transition layer is a continuous gradient layer formed by integral co-extrusion of at least three semi-conductive polyolefin-based composite melts with different compositions in radial order, and retained after cross-linking and segmented cooling. The at least three semiconductive polyolefin-based composite melts adopt the same polyolefin matrix system, and adjacent semiconductive polyolefin-based composite melts form a continuous transition connection during the integral co-extrusion process. The semi-conductive polyolefin-based composite material used in the gradient compatibility buffer transition layer includes a polyolefin matrix, conductive fillers, and compatibility components. The gradient compatibility buffer transition layer, along its thickness direction from the side near the insulating layer to the side near the insulating shielding layer, exhibits a continuous monotonically decreasing content of compatibility components, a continuous monotonically increasing content of conductive fillers, and a continuous monotonically decreasing volume resistivity. The continuous monotonically decreasing and continuous monotonically increasing parameters both indicate that the corresponding parameters change continuously along the thickness direction, and do not change in the opposite direction to their corresponding changes. The gradient compatibility buffer transition layer does not have a layered interface formed by the solidification of the at least three strands of semiconductive polyolefin-based composite melt, and the gradient compatibility buffer transition layer and the insulating layer, as well as the gradient compatibility buffer transition layer and the insulating shielding layer, are all direct fusion bonding interfaces.

2. The medium- and high-voltage cable as described in claim 1, characterized in that, The thickness of the gradient compatibility buffer transition layer is 0.05–0.12 mm; By weight, the semi-conductive polyolefin-based composite material comprises 55-75 parts of polyolefin matrix, 20-30 parts of conductive filler and 6-12 parts of compatible component; The compatible components include 5-10 parts grafted maleic anhydride polyethylene and 1-3 parts surface-modified nano silica.

3. The medium- and high-voltage cable as described in claim 2, characterized in that, The polyolefin matrix includes low-density polyethylene and linear low-density polyethylene, and the mass ratio of the low-density polyethylene to the linear low-density polyethylene is 6:4 to 7:3; the conductive filler is acetylene black. The surface-modified nano-silica has a particle size of 20–30 nm, and the modification method is plasma treatment or silane coupling agent modification.

4. The medium- and high-voltage cable as described in claim 1, characterized in that, Along the thickness direction of the gradient compatibility buffer transition layer, a first detection position is selected near the side of the insulating layer, a second detection position is selected in the middle of the thickness direction, and a third detection position is selected near the side of the insulating shielding layer. The content of the compatible component at the first detection position is higher than the content of the compatible component at the second detection position, and the content of the compatible component at the second detection position is higher than the content of the compatible component at the third detection position; The conductive filler content at the first detection position is lower than the conductive filler content at the second detection position, and the conductive filler content at the second detection position is lower than the conductive filler content at the third detection position; The first detection position, the second detection position, and the third detection position represent the continuous gradient change of the gradient compatible buffer transition layer along the thickness direction, and do not constitute mutually independent layered structures.

5. The medium- and high-voltage cable as described in any one of claims 1 to 4, characterized in that, The volume resistivity of the gradient compatibility buffer transition layer near the insulating layer is 8.0 × 10⁻⁶. 4 ~1.3×10 5 The volume resistivity of the gradient compatibility buffer transition layer near the insulating shielding layer is 8.0 × 10 Ω·cm. 2 ~2.0×10 3 Ω·cm.

6. A method for preparing the medium- and high-voltage cable according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Provide a conductor and extrude a conductor shielding layer outside the conductor; S2. Using a split-feed co-extrusion process, an insulating layer, a gradient compatibility buffer transition layer, and an insulating shield layer are integrally formed outside the conductor shield layer. The at least three semiconductive polyolefin-based composite melts forming the gradient compatibility buffer transition layer use the same polyolefin matrix system and are fed into the confluence and composite zone through at least three independent flow channels in the co-extrusion die head, and are melt-composite in a radial order from the side closest to the insulating layer to the side closest to the insulating shield layer. The content of the compatible component in the at least three semiconductive polyolefin-based composite melts decreases sequentially in the radial order, and the content of the conductive filler increases sequentially in the radial order. The temperature of each independent flow channel and the feed flow rate of each semiconductive polyolefin-based composite melt are set differently according to the radial order, so that each semiconductive polyolefin-based composite melt melt melts and composites radially in the co-extrusion die head, and forms a continuous transition connection between adjacent semiconductive polyolefin-based composite melts. S3. Perform cross-linking treatment on the cable core obtained in step S2; S4. Perform segmented cooling treatment on the cable core after cross-linking treatment in step S3. The segmented cooling treatment includes a first stage cooling and a second stage cooling. The first stage cooling is a stress relief and slow cooling stage, and the second stage cooling is a rapid shaping cooling stage. The cooling rate of the first stage is lower than that of the second stage cooling. The first stage of cooling is used to reduce the radial shrinkage difference of the cross-linked cable core and the concentration of interfacial thermal stress, while the second stage of cooling is used to quickly shape the continuous gradient distribution and fusion bonding interface after the interfacial thermal stress is relieved. S5. The cable core after step S4 is degassed, and a metal shielding layer, an inner lining layer, an armor layer and an outer sheath layer are formed sequentially on the outside of the degassed cable core.

7. The method as described in claim 6, characterized in that, In step S2, the semiconductive polyolefin-based composite melt forming the gradient compatibility buffer transition layer consists of three strands, which are arranged radially as the first melt, the second melt, and the third melt. The three independent flow channels into which the first melt, the second melt, and the third melt respectively enter are the first independent annular flow channel, the second independent annular flow channel, and the third independent annular flow channel arranged in sequence along the radial direction of the cable core. The outlets of the first independent annular flow channel, the second independent annular flow channel, and the third independent annular flow channel are all connected to the same annular confluence and composite area. The first melt, the second melt, and the third melt maintain molten contact within the annular confluence and composite zone and undergo controlled molten composite and interface broadening, forming molten composite regions with gradually transitioning compositions between the first melt and the second melt, and between the second melt and the third melt.

8. The method as described in claim 7, characterized in that, In step S2, the temperature of the first independent annular flow channel is 111-115°C, the temperature of the second independent annular flow channel is 108-112°C, and the temperature of the third independent annular flow channel is 105-109°C. The co-extrusion die head temperature is 108–112℃, the melt pressure is 22–28MPa, and the traction speed is 9–11m / min; The shear rate ratio of the first melt, the second melt, and the third melt is 1.0:1.1~1.3:1.4~1.

6.

9. The method according to any one of claims 6 to 8, characterized in that, In step S4, the first stage of cooling uses circulating hot water for slow cooling, reducing the cross-linked cable core to 118-130°C at a cooling rate of 0.5-1.2°C / s; The second stage of cooling uses room temperature water spraying or water tank cooling to cool the cable core after the first stage of cooling to room temperature at a cooling rate of 2.5 to 5.0℃ / s.

10. The method according to any one of claims 6 to 9, characterized in that, Step S3 uses peroxide vapor crosslinking; step S5 uses vacuum degassing. The metal shielding layer is a copper wire loosely wound metal shielding layer, the inner lining layer is a PVC inner lining layer, the armor layer is a galvanized steel strip armor layer, and the outer sheath layer is a high-density polyethylene outer sheath layer.

Citation Information

Patent Citations

  • The water-blocking type shielding structure is suitable for medium-voltage single-core cables

    CN213025506U

  • Electrical element comprising a layer of a polymeric material having an electrical conductivity gradient

    US20140246220A1